26 TGF-beta induced interaction of human MSC coculture with HNSCC cell line PCI-13. Issue 5 (May 2015) - ,; Aeckerle, N.; Kramer, F.-J.; Schliephake, H.; Böhrnsen, F.
Abstract : Introduction: Stromal and tumor cell interactions are influenced by growth factors like TGF-beta and determine cancer progression. In this microenvironment epithelial-mesenchymal transition (EMT) of tumor cells leads to a loss of cellular integrity which affects invasion, progression and metastasis of head and neck squamous cell carcinoma (HNSCC). In this study, we are testing the hypothesis that TGF-beta is able to guide the interactions of human mesenchymal stromal cells (MSC) with HNSCC, influencing the expression of markers of EMT and tumor progression in transwell co-culture of human MSC with the HNSCC cell line PCI-13. Material and methods: Pooled MSCs were derived from the iliac bone marrow of 7 patients and co-cultured in trans-well permeable membrane wells with tumor cells of the established HNSCC cell line PCI-13 (UICC: T3, N1, M0) under the influence of 20 ng/ml TGF-beta. MSCs were characterized through FACS analysis. Expression of E-Cadherin and Vimentin was analyzed via immunofluorescence and the expression of Wnt3, MMP14, beta-catenin, E-cadherin, Vimentin, Snail1, Twist and MMP3 assessed by quantitative RT-PCR. Changes in the AKT-Signaling pathway were analyzed via chemiluminescent assay. Results: We were able to show that TGF-beta did not influence the expression of E-Cadherin in PCI-13. However we observed an increase of the EMT marker Vimentin. MSC demonstrated an increase in E-Cadherin but no changes in Vimentin expression. We were able to show that co-culture of MSCs and PCI-13 leads to a reduced expression of Wnt3, MMP14 as well as beta-catenin compared to controls. AKT-signaling analysis revealed a high phosphorylation of PRAS40, PTEN and 4E-BP1 in both, MSC and PCI-13. In addition the PCI-13 shows a high phosphorylation of Bad. Conclusion: Our results suggest that TGF-beta is able to affect the interactions between MSCs and PCI-13 leading to a mesenchymal shift in PCI-13 while increasing the cellular integrity of the surrounding stromal tissue. This dual influence initiates the onset of EMT in HNSCC/PCI-13 while increasing stromal adhesion in MSC.